2009
DOI: 10.1007/s10561-009-9128-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum eye drops, amniotic membrane and limbal epithelial stem cells—tools in the treatment of ocular surface disease

Abstract: The advent of serum eye drops, amniotic membrane and limbal stem cell grafts, have transformed the treatment of diseases which result in ocular surface failure. This article provides an overview of ocular surface anatomy and failure, and how the use of serum eye drops, amniotic membrane and limbal epithelial stem cell transplantation has influenced ophthalmological practice both historically and in recent years. This review focuses on the rationale for the use of these emerging tools, how they are prepared, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 38 publications
(35 reference statements)
0
64
0
1
Order By: Relevance
“…The main drawbacks are the fact that the patient has to be medically suitable to donate blood, the screening process, and the cost. Also there is a risk that as a blood product, autologous serum could carry unknown infection [Rauz and Saw, 2010]. In this review, 23 studies used fetal calf serum and 7 used autologous serum, with 2 using both (in different patients; Table I).…”
Section: Serum In Culture Mediummentioning
confidence: 99%
“…The main drawbacks are the fact that the patient has to be medically suitable to donate blood, the screening process, and the cost. Also there is a risk that as a blood product, autologous serum could carry unknown infection [Rauz and Saw, 2010]. In this review, 23 studies used fetal calf serum and 7 used autologous serum, with 2 using both (in different patients; Table I).…”
Section: Serum In Culture Mediummentioning
confidence: 99%
“…Many studies have revealed amniotic membrane transplantation as a temporary or permanent graft that induces epithelial wound healing. It also possesses anti-inflammatory and anti-scarring effects on the ocular surface 11,13) . Because of these beneficial effects, amniotic membranes are clinically used as a graft or a patch-in severe case of ocular surface disease.…”
Section: Discussionmentioning
confidence: 99%
“…Human amniotic membrane extracts (HAEs) consist of a variety of molecules such as sugars, lipids, proteins, and peptides 11) . Many studies have reported that the function of the amniotic membrane is known to exert anti-inflammation and anti-scarring effects and promote epithelial wound healing [11][12][13] . Also, amniotic epithelial cells are reported to secrete immunosuppressive factors in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the similarities between the constituents of and the natural (whole) tear film as shown in Table 3. 7 Since the first reported use of autologous serum eye drop (auto-SED) by Fox in 1984, 8 SED have demonstrated to be effective for the treatment of complex dry eye disease secondary to a wide range of clinical conditions causing OSD (Stevens-Johnson syndrome, Sjögren's syndrome, persistent epithelial defects, graft-vs-host disease, post-LASIK dry eyes, neurotrophic keratopathy, diabetes mellitus, superior limbic keratoconjunctivitis, recurrent corneal erosions, aniridic limbal stem cell deficiency), and supportive therapy for ocular surface reconstruction and stem cell therapy. Demand for the service has been steadily increasing but access to care has been restricted due to a number of multifactorial reasons including licensing status and cost.…”
Section: Current Practicementioning
confidence: 99%